2001
DOI: 10.1016/s0735-1097(01)01167-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic assessment of coronary artery stenosis by coronary flow reserve measurements with transthoracic doppler echocardiography: comparison with exercise thallium-201 single-photon emission computed tomography

Abstract: Noninvasive measurement of CFR by TTDE provides data equivalent to those obtained by Tl-201-SPECT for physiologic estimation of the severity of LAD stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 25 publications
3
64
0
4
Order By: Relevance
“…For example, in the presence of right ACAOS, a normally originating prominent conal branch could be misinterpreted as a normally originating RCA. Some operators have recently reported a new capacity to evaluate anterior coronary vessels for severity of obstruction by means of contrast-enhanced, color-guided, pulsed-wave Doppler-flow interrogation during transthoracic echocardiography [16,17]; this development may be of interest with respect to future applications in ACAOS.…”
Section: Echocardiographymentioning
confidence: 99%
“…For example, in the presence of right ACAOS, a normally originating prominent conal branch could be misinterpreted as a normally originating RCA. Some operators have recently reported a new capacity to evaluate anterior coronary vessels for severity of obstruction by means of contrast-enhanced, color-guided, pulsed-wave Doppler-flow interrogation during transthoracic echocardiography [16,17]; this development may be of interest with respect to future applications in ACAOS.…”
Section: Echocardiographymentioning
confidence: 99%
“…Many more confounding factors may arise: the main one is certainly the microcirculatory dysfunction. TTE-CFR can be used in clinical practice to collect data comparable with that from invasive tests 30 . CFR normality cutoff is >2.…”
Section: Coronary Flow Reserve and Epicardial Coronary Stenosesmentioning
confidence: 99%
“…Several recent studies have shown that coronary flow velocity (CFV) in the distal part of the left anterior descending coronary artery (LAD) can be successfully measured by transthoracic Doppler echocardiography (TTDE), and the measurement of coronary flow velocity reserve (CFVR) with adenosine or dipyridamole has been shown to be a useful index for detecting functionally significant LAD stenosis. [10][11][12] method also may be useful for the serial assessment of CFVR in the same patients. It is uncertain whether or not coronary microvascular dysfunction in diabetic patients is irreversible with hypoglycemic therapy.…”
mentioning
confidence: 99%